The War on Terror and the Laws of War: A Military Perspective - Ben Stanford (Utrecht Journal of International and European Law, 2015)
In this well-timed revision to the first edition published in 2009, the authors allow the reader to benefit from their unique yet balanced perspectives as they address some of the most pressing issues in the enduring campaign to defeat terrorism insofar as they concern the laws of war. The six authors, all of whom served in some capacity in the Armed Forces of the United States of America (USA), confess not to provide a critical analysis of the official characterisation of the ‘War on Terror’ as a genuine armed conflict under international humanitarian law. A reader expecting such an approach should invest their time and attention elsewhere. Whilst acknowledging that ‘it is clear that the term “war on terror” is legally and operationally overbroad and misleading’,1 the authors choose to ground their contributions on the basis that the USA has operated, and continues to operate, as if it were in an armed conflict with al-Qaeda and its associated groups. According to the authors, this stance is justified by the argument that the three branches of government of the USA have repeatedly and consistently reached decisions to this effect. As a result, many readers might be inclined to approach the book with caution at first. This fundamental stance is however well-noted, emphasised, and indeed reasonable as the authors approach the controversial subjects from a factual, and most importantly, a military perspective.